2018
DOI: 10.1136/gpsych-2018-100003
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Peony-Glycyrrhiza decoction for antipsychotic-induced hyperprolactinaemia: a meta-analysis of randomised controlled trials

Abstract: BackgroundHyperprolactinaemia is a common adverse effect of antipsychotics (APs). The results of Peony-Glycyrrhiza decoction (PGD) as a potentially useful adjunctive treatment for hyperprolactinaemia are inconsistent.AimThis meta-analysis of randomised controlled trials (RCTs) examined the efficacy and safety of adjunctive PGD therapy for AP-induced hyperprolactinaemia.MethodsEnglish (PubMed, Embase, Cochrane Library, PsycINFO) and Chinese (Chinese National Knowledge Infrastructure, Wanfang Data) databases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The advantage of ARI, and PGD in reducing HPRL is consistent with previous researches [ 33 , 35 , 38 ]. The NMA of Zhang L et al compared the efficacy among ARI, PGD and MET, it indicated that adjunctive ARI (<5 mg) was associated with the most significant reduction in prolactin levels compared to placebo; they also found that adjunctive PGD had the most significant effect in reducing risperidone-induced HPRL; furthermore, adjunctive aripiprazole (<5 mg) had the most significant effect in reducing amisulpride-induced HPRL, while the result was imprecise [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…The advantage of ARI, and PGD in reducing HPRL is consistent with previous researches [ 33 , 35 , 38 ]. The NMA of Zhang L et al compared the efficacy among ARI, PGD and MET, it indicated that adjunctive ARI (<5 mg) was associated with the most significant reduction in prolactin levels compared to placebo; they also found that adjunctive PGD had the most significant effect in reducing risperidone-induced HPRL; furthermore, adjunctive aripiprazole (<5 mg) had the most significant effect in reducing amisulpride-induced HPRL, while the result was imprecise [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…org) based on the PRISMA statement. 50 Standardised mean differences (SMDs) with their 95% CIs and risk ratios (RRs) with its 95% CIs were calculated. SMD values over 0.8, 0.5-0.8 and 0.2-0.5 represented large, medium and small effect sizes, respectively.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…18 Currently, the evidence supporting the use of PGD in the treatment of antipsychotic-induced hyperprolactinemia is limited. The conclusion of a meta-analysis that included five randomized controlled trials supports the adjunctive use of PGD in patients with hyperprolactinemia; 19 however, the authors also acknowledge that the evidence included has some limitations, and further experiments are still needed to verify the effectiveness of PGD for hyperprolactinemia.…”
Section: Introductionmentioning
confidence: 97%